PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PADA DINAS SOSIAL KABUPATEN SITUBONDO) - Muhamad Badrianto; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study to determine and analyze the influence of Leadership, Work environmen, and Motivation on the performance of cifil servants in the social service of Situbondo Regency. The population used in this study were all empolyees of the Social Service Office of Situbondo Regency with a sample of 35 employees whilw the data collection distributed questionnaires. This study uses data analysis, a) validity test b)reliability test c) normality test d) multicollinearity test e) heterocedasticity f) multiple linear analysis g) hypotesis testing. This study uses a saturated sampling technique or with an explanation(census).The results showed that partially there was no significant effect between leadership on employee performance, the work environment did not have a significant effect on employee performance and Motivation had a significant effect on empolyee performance at the Social service of Situbondo Regency. While the simultaneous test result show that Leadership, Work Environment, and Motivation significant effect towards the performance of cifil servants in the Social of Situbondo Regency. Keywords : Leadership, Work Environment, Motivation, and Performance